Path analysis and estimation of additive and epistatic gene effects of barley SSD lines - Jan Bocianowski; Katarzyna Górczak; Kamila Nowosad; Wojciech Rybiński; Dariusz Piesik (Journal of Integrative Agriculture, 2016)
In the paper presented, 99 single seed descent barley lines as well as their parental forms Roland and Apex were studied. The grain weight components and their interrelations were analyzed using simple coefficients of correlation. The direct and indirect effects of such components on grain weight per plant and 1000-grain weight were estimated using path analysis. In the 2006 and 2007, the spike length and number of spikelets per spike were the determinants of grain weight. Genetic parameters as additive and epistasis effects were estimated for all studied traits. The results indicate the importance of both additive and epistasis gene effects of number of spikes per plant, grain weight per spike, grain number per plant and grain weight per plant in this study.